Social distance, immigrant integration, and welfare chauvinism in Sweden - Tina Goldschmidt; Jens Rydgren (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2018)
Populist radical right-wing parties across Europe garner support for welfare chauvinistic promises to limit government spending on immigrants and focus on natives' welfare instead. However, most research on the so-called immigration-welfare nexus does not study welfare chauvinism but instead focuses on generalized support for the welfare state. Using Swedish register-linked survey data from 2013, we study three hypothetical pathways into welfare chauvinism: via ethnic prejudice, operationalized as a desire for social distance; via the direct experience of immigrant unemployment and putative welfare receipt in the neighborhood context; and via immigrant competition at the workplace. Based on our sample of native-born Swedes, we find that both negative prejudice and the share of unemployed immigrants among the neighborhood population provide two distinct and independent routes into chauvinism, while workplace competition does not.
Keywords: 300; welfare chauvinism; government spending; immigration; integration; prejudice; Sweden